Disentangling workplace sexism in age generations: A multi-group analysis on the effects on job satisfaction and task performance - Martina Morando (Administrative Sciences, 2023)
The gender gap is a current topical issue. Sexist assumptions that manifest as gender stereotypes are partially responsible for these inequalities. The ambivalent sexism theory argues that hostile sexism refers to explicitly antagonistic sexist attitudes, while benevolent sexism refers to apparently positive but implicitly malevolent attitudes. There has been evidence reported that benevolent sexism is detrimental to women's personal and professional well-being, implies lower levels of career aspiration and impacts task performance. This study is aimed at examining the impact that the experience of benevolent and hostile sexism could have on performance and job satisfaction. A total of 402 female workers were enrolled. The results showed that an experience with benevolent sexism significantly decreased the positive relationship between work engagement, psychological capital and organisational support and outcomes. Conversely, hostile sexism only reduces job satisfaction in its interaction with work engagement and organisational support. Moreover, through a multi-group analysis, possible differences across age were examined in the theorised model. Here, the younger generation seems to be more affected and experience more benevolent sexism than the older generation, which is seen both in individual moderators and in their interactions with predictors. This study is helpful for a deeper comprehension of contemporary sexism, offering also suggestions for equality policies' design.
Keywords: 350; sexism; gender equality; social sustainability; satisfaction; performance